2011
DOI: 10.1294/jes.22.29
|View full text |Cite
|
Sign up to set email alerts
|

Annual Changes in Day-length, Temperature, and Circulating Reproductive Hormones in Thoroughbred Stallions and Geldings

Abstract: Changes in follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, immunoreactive(ir)-inhibin, testosterone, estradiol-17β, and insulin-like growth factor (IGF)-I in Thoroughbred stallions along with changes in prolactin secretion in geldings were studied. The correlations of day-length with changes in the concentrations of these hormones were also studied. Five stallions and thirteen geldings were employed to draw blood samples in monthly basis and radioimmunoassay was performed to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
(25 reference statements)
2
30
0
Order By: Relevance
“…In our experiments, prolactin in both sexes correlated positively with the day length. In fact, an earlier study [1] in stallions and geldings showed that the correlation is stronger with the daylength than with temperature. It is a known fact that melatonin secretion is lower during increasing photo periods.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In our experiments, prolactin in both sexes correlated positively with the day length. In fact, an earlier study [1] in stallions and geldings showed that the correlation is stronger with the daylength than with temperature. It is a known fact that melatonin secretion is lower during increasing photo periods.…”
Section: Discussionmentioning
confidence: 90%
“…The intra-and interassay coefficients of variance were 8.0% and 16.2%, respectively. The plasma concentration of prolactin was measured by RIA using rat anti-sera against equine prolactin (AFP-261987) and a reference standard (AFP-8794B) as previously described [1]. The intra-and interassay coefficients of variance were 7.1% and 9.8% respectively.…”
Section: Radioimmunoassay Of Fsh Lh Ir-inhibin Testosterone Progementioning
confidence: 99%
See 2 more Smart Citations
“…The measurement method for PRL in mare plasma was constructed using a homologous radioimmunoassay system as described previously [8], using a rat anti-sera against equine PRL (AFP261987) and iodinated equine PRL (AFP8794B) and reference standard (AFP7730B) (provided by Dr. A. F. Parlow). The intra-and inter-assay coefficients of variation were 4.3 and 8.7%, respectively.…”
Section: Experiments 1: Case Report On the Induction Of Lactation And mentioning
confidence: 99%